Study the Effect of Using Learning Cycle Strategy on Achievement of First Year Students in Arabic Grammar at Al-Qasim Green University/ College of Environmental Science - al-Mamouri, Mousa Kadhim Zqair (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at investigating the effect of using (5Es) Learning Cycle Strategy on achievement of first year students in Arabic grammar at Al-Qasim Green University/ College of Environmental Science. In order to achieve the aim of this study, the researcher randomly selected the College of Environmental Science that is one of the colleges at Al-Qasim Green University; the researcher used a partially experimental design. The sample of the study made up of (60) students (30 students in experimental group and 30 students in the control group). The researcher equivalents between the two study groups in the following variables: age by months, the marks of Arabic grammar in the previous semester, the academic performance of parents, there was no statistically significant differences at (0.05). After determining the scientific topic (the experimental topics), the researcher formed a behavioral objectives of the specific topics, and after presenting these objectives in its essential form to a number of experts and specialists in the methods of teaching Arabic language to validate its validity, which reached to (20) behavioral objectives in its final form. When the experience has been conducted, the researcher taught himself the two study groups from 1/10/2018 to 28/1/2019. After preparing an objective achievement test consisting of (20) items in their final form characterized by validity and stability, the researcher applied it to a sampling survey of (30) students in another college (College of Agriculture - Al-Qasim Green University). After applying the summative assessment on the sample of this study, the researcher dealt with data statistically by using t- test. After getting the final results, the results showed that the students of the experimental group who have studied Arabic grammar by using the learning cycle strategy are better than the students of the control group who have studied Arabic grammar by using the traditional method, the differences were statistically significant at the level of (0.05). Through the results of this study, the researcher recommended that “it is necessary to use (5Es) Learning Cycle Strategy in teaching Arabic grammar”. As a complement to this study, the researcher suggested conducting a similar study on other departments in different colleges.